Cognitive Screening in Speech-Language Pathology and Audiology: Outcomes of an Interdisciplinary Workshop for Preservice Clinicians. - Anjum, Javad; Washnik, Nilesh; Parveen, Sabiha; Feltis, Ann (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: Prompt screening, assessment, and interdisciplinary management of mild cognitive impairment and early-stage (mild) dementia are essential for delaying progression into severe cognitive impairment and improving life participation. Previous studies have primarily focused on the knowledge of cognitive screening among health care professionals and community-dwelling older adults. There is limited research regarding training of preservice clinicians in this area within speech-language pathology (SLP) and audiology (AuD) or on their engagement in interdisciplinary collaborations related to cognitive screening. The primary purpose of the current study was to examine the effectiveness of an active learning-based interdisciplinary training workshop in improving the knowledge, attitudes, and self-efficacy of graduate students in speech-language pathology and AuD for integrating cognitive screening for older adults into their future clinical practice. Method: A total of 55 graduate students (speech-language pathology = 38, AuD = 17) at a large public university in the United States participated in a 2-hr active learning-based interdisciplinary training workshop conducted by SLP and AuD faculty members. Pre- and post-workshop data were collected through structured questionnaires, which included Likert-type items and open-ended questions. Results and Conclusions: Pre-post comparative analysis showed significant improvements in foundational knowledge, a positive shift in attitudes regarding inclusion of cognitive screening in clinical practice, and enhanced self-efficacy in administering cognitive screening tests. Results underscore the role of interdisciplinary training in augmenting the knowledge and preparedness of future speech-language pathologists and audiologists working with older adults with and without cognitive decline.